Newborn with nonimmune hydrops fetalis - the experience of a tertiary center. - Teixeira, Ana (2008)
Nonimmune hydrops fetalis is a rare affection that can result from several disorders. Notwithstanding with the advances in the diagnosis and treatment, its morbidity and mortality are still very high. The purpose of this study was to characterize the newborn population with nonimmune hydrops fetalis admitted to our unit during the last ten years.A descriptive review of the newborns with nonimmune fetalis hydrops admitted to the Neonatal Intensive Care Unit of Hospital de São João, between 1997 and 2006. Data on pregnancy, delivery, perinatal approach, etiological evaluation and outcome were collected.Nineteen neonates (9M/10F) with a median gestational age of 32 weeks (26-39) and a median birth weight of 2695 g (884-4270) were studied. Sixteen (84%) were preterm. Antenatal diagnosis was made in fourteen (74%) cases, and two received in uterus treatment. C-section was performed in fourteen (74%) cases. Sixteen (84%) neonates needed resuscitation in the delivery room. Aetiological diagnosis was made in 89% (n = 17): cardiovascular (n = 5), haematological (n = 5), metabolic (n = 2), infectious (n = 2), chromosomal (n = 1), lymphatic malformation (n = 1) and meconium peritonitis (n = 1). The median length of hospital stay was 17 days. Thirteen (68%) neonates were deceased.The occurrence and admission of newborns with nonimmune hydrops fetalis to our unit was rare. The aetiological diagnosis was made in 89% and mortality rate was 68%. The worse prognosis was related to preterm birth, anaemia, cardiac malformation, metabolic disorder, congenital infection and chromosomopathy. The prompt aetiological diagnosis and its proper ante and postnatal management are the most important steps to reduce the morbidity and mortality of this condition.